Detection of Some Aflatoxins in Some Locally Marketed Walnut Samples - ياسين, مفيد; ياسين, سندس; خليل, ريما (Latakia University Journal -Medical Sciences Series, 2020)
Walnuts are nuts known for their high nutritional value and delicious taste, but they can pose a serious health hazard due to their high possibility of contamination with aflatoxins. Aflatoxins are produced as secondary metabolites in foods that are affected by some fungal species; eating these foods may cause cancer and mutations. This research aims to investigate the presence of aflatoxins in 20 samples of walnuts marketed in Lattakia governorate. AFs were determined using High Performance Liquid Chromatography (HPLC) connected to Fluorescence Detector (FLD); and that was done after extraction of samples with 70% methanol and purification using an immunoaffinity column (IAC). The results showed that 20% of the walnut samples were contaminated with aflatoxins, and the concentration of total aflatoxins and AFB1 in all the contaminated samples was less than the limits allowed by the European Union and the Syrian Standard Specification, which is 4 µg/kg and 2 µg/kg in the same previous order. The concentrations of total aflatoxins in the studied walnut samples were within the range (0.7-2.86) µg/kg with an average ± SD (0.89 ± 1.69) µg/kg, while AFB1 was found within the range (0.7-1.76) µg/kg with an average ± SD (1.31 ± 0.54) µg/kg. The appearance percent of the four types of aflatoxins in our studied samples was (15%) for aflatoxin B1, (5%) for aflatoxin B2, (5%) for aflatoxin G1 and (0%) for aflatoxin G2.